Massive WDM and TDM soliton transmission systems : a ROSC symposium - Hasegawa, Akira, 1934- (Solid-state science and technology library, 2002)
This book summarizes proceedings of the invited papers presented at the International Symposium on Massive WDM and TDM Soliton Transmission Systems held in Kyoto, Japan in the fall of 1999. The symposium is the third of the series and is considered to be the most representative symposium on the subject of use of optical solitons for ultrafast communications. In particular, this symposium focuses on the newly developed technologies of dispersion managed soliton transmission capabilities. Studies of properties of new solutions that appear in fibers with periodic variation of dispersion are also presented.